Optimization of KNO3 Concentration in Breaking Dormancy and Enhancing Seed Vigor of Hevea brasiliensis - Yan Piter Basman Ziraluo (Program Studi Pendidikan Biologi - Universitas Nias, 2026)
Seed dormancy remains one of the major constraints affecting the propagation and seedling availability of Hevea brasiliensis in rubber cultivation systems. Low germination percentage and poor seed vigor often reduce seedling quality and hinder plantation productivity. This study aimed to determine the optimal concentration of Potassium Nitrate (KNO3) in breaking seed dormancy and enhancing seed vigor of Hevea brasiliensis. The study was conducted using a Completely Randomized Design (CRD) consisting of five treatments, namely 0%, 10%, 20%, 30%, and 40% KNO3 concentrations with four replications. Rubber seeds were soaked in KNO3 solutions for 72 hours and observed for 60 days. Parameters measured included germination percentage, germination rate, plumule length, and root length. Data were analyzed using One-Way Analysis of Variance (ANOVA) followed by Least Significant Difference (LSD) and Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that KNO3 treatment significantly affected dormancy breaking and seed vigor enhancement. The 40% KNO3 treatment produced the highest germination percentage, fastest germination rate, and best seedling growth performance compared to other treatments. These findings indicated that KNO3 application effectively stimulated germination activity and improved the physiological quality of rubber seeds.